Online Catering Booking Application Based on Web-Based and Mobile Budget - Amanda Aprilina; Anna Dina Kalifia (Komunitas Dosen Indonesia, 2025)
The rapid advancement of information technology has encouraged digital transformation across various service industries, including the catering sector. Many small and medium enterprises (SMEs) still rely on manual ordering systems that often lead to data inaccuracies and inefficient service operations. To address these challenges, digital-based solutions are needed to streamline transactions, improve service accuracy, and enhance customer experience. This study aims to develop an integrated web and mobile-based catering ordering information system equipped with a budget-based ordering feature that allows users to select menus according to their financial capacity. The system was developed using the Waterfall model as the main framework, encompassing stages of requirement analysis, system design, implementation, and testing. The backend was built with Laravel framework, while the mobile application used React Native, ensuring real-time synchronization through a centralized API. The interface design applied Bootstrap and CSS to achieve responsiveness and usability across devices. System testing was conducted using the Blackbox Testing method to evaluate functional accuracy from the user’s perspective. Unlike previous systems that focus only on integration, this study introduces a budget-based filtering mechanism that dynamically adjusts menu recommendations to user-defined spending limits, enhancing personalization and affordability. The implementation results show that the system operates effectively and consistently across both platforms, enabling seamless order, payment, and confirmation processes. In conclusion, the proposed system successfully combines cross-platform integration with budget-based personalization, providing an efficient, reliable, and adaptable model for digital transformation in catering service management.